Sosialisasi dan Problem Solving Keterlambatan Pengembalian Berkas Rekam Medis dengan Diagram Fishbone - Ibrahim, Mochammad Malik; Yusmanisari, Eka; P, Ria Irmanda; Anafiah, Fitri (STIKES Yayasan RS.Dr.Soetomo, 2024)
The problem of delays in returning inpatient medical record files in the Ashoka Room in December was the highest with a return time of 18 days. This service aims to provide an understanding of the flow of returning medical records and solving the problem of delays in returning medical record files. This service activity is carried out in several stages. The results obtained by participants were able to understand the flow of returning inpatient medical record files which had been socialized and became a poster output product in this service and were also presented in the socialization regarding problem solving for delays in returning inpatient medical record files at Bangil Regional Hospital using a Fishbone diagram. Suggestion: It is necessary to make efforts to monitor and evaluate the implementation of the SOP for returning medical record files, resocialize the SOP to remind health workers about the time to return medical record files, provide motivation or praise in the form of a certificate of appreciation to health workers who are responsible for returning medical record files on time.